Microbiological Quality and Resistance to an Artificial Gut Environment of Two Probiotic Formulations - Diletta Mazzantini; Francesco Celandroni; Marco Calvigioni; Adelaide Panattoni; Roberto Labella; Emilia Ghelardi (Foods, 2021)
The quality control of probiotic products is the focus of numerous organizations worldwide. Several studies have highlighted the poor microbiological quality of many commercial probiotic formulations in terms of the identity of the contained microorganisms, viability, and purity, thus precluding the expected health benefits and representing a potential health risk for consumers. In this paper, we analyzed the contents of two probiotic formulations, one composed of an encapsulated mixture of lactobacilli and bifidobacteria, and one by a lyophilized yeast. The microorganisms contained in the products were quantified and identified using up-to-date methodologies, such as MALDI-TOF MS and metagenomic analysis. Moreover, as acid and bile tolerance is included among the criteria used to select probiotic microorganisms, in vitro tests were performed to evaluate the behavior of the formulations in conditions mimicking the harsh gastric environment and the intestinal fluids. Our results indicate the high quality of the formulations in terms of the enumeration and identification of the contained organisms, as well as the absence of contaminants. Moreover, both products tolerated the acidic conditions well, with encapsulation providing further protection for the microorganisms. A good tolerance to the simulated artificial intestinal conditions was also evidenced for both preparations.